Pathogenicity Testing of Several APEC Isolates Obtained from Naturally Infected Broiler Birds Reared in Basrah - AL-Saiedi , Ruaa L.R.; Al-Mayah, Ali A.S. (International Journal of Poultry Science, 2014)
The present study was conducted to investigate the in vitro and in vivo virulence of several E. coli isolates which have been obtained from naturally infected broiler birds. Fifty seven dead and other morbid birds were collected from Al-Basra markets and Basra Veterinary Hospital. A total of 140 sterile cotton swabs from fibrinous pericarditis, fibrinous perihepatitis and airsacculitis were taken and subjected for bacteriological examinations. The result revealed that the overall identification rate of E. coli was (37.5%). To differentiate between pathogenic and nonpathogenic isolates, several in vitro and in vivo pathogenicity testing were performed. Congo Red binding activity showed that 60% were positive, whereas motility test displayed that 51.85% were motile. The ability of isolated E. coli to produce hemolysin was found that 44.6% of these isolates were hemolytic. Hemagglutination test indicated that 3.70% of the present isolates were positive. The results of in vitro testing indicated that 3 isolates were classified as highly, moderately and slightly virulent according to their characteristics of pathogenicity. In vivo, one day old chick lethality test indicated that almost all the three tested E. coli isolates which had been inoculated S/C were caused mortality of these chicks within 12-96 h. Three weeks old broiler birds which have been intratracheally inoculated with E. coli were clearly displayed characteristic pathological lesions ranging from typical double sided airsacculitis, fibrinous pericarditis and fibrinous perihepatitis to mild one sided airsacculitis.